Subgenome evolutionary dynamics in allotetraploid ferns: insights from the gene expression patterns in the allotetraploid species Phegopteris decursivepinnata (Thelypteridaceae, Polypodiales) - Katayama, Natsu; Yamamoto, Takuya; Aiuchi, Sakura; Watano, Yasuyuki; Fujiwara, Tao (Frontiers in Plant Science, 2024)
Allopolyploidization often leads to disruptive conflicts among more than two sets of subgenomes, leading to genomic modifications and changes in gene expression. Although the evolutionary trajectories of subgenomes in allopolyploids have been studied intensely in angiosperms, the dynamics of subgenome evolution remain poorly understood in ferns, despite the prevalence of allopolyploidsization. In this study, we have focused on an allotetraploid fern-Phegopteris decursivepinnata-and its diploid parental species, P. koreana (K) and P. taiwaniana (T). Using RNA-seq analyses, we have compared the gene expression profiles for 9,540 genes among parental species, synthetic F1 hybrids, and natural allotetraploids. The changes in gene expression patterns were traced from the F1 hybrids to the natural allopolyploids. This study has revealed that the expression patterns observed in most genes in the F1 hybrids are largely conserved in the allopolyploids; however, there were substantial differences in certain genes between these groups. In the allopolyploids compared with the F1 hybrids, the number of genes showing a transgressive pattern in total expression levels was increased. There was a slight reduction in T-dominance and a slight increase in K-dominance, in terms of expression level dominance. Interestingly, there is no obvious bias toward the T-or K-subgenomes in the number and expression levels overall, showing the absence of subgenome dominance. These findings demonstrated the impacts of the substantial transcriptome change after hybridization and the moderate modification during allopolyploid This is a provisional file, not the final typeset article establishment on gene expression in ferns and provided important insights into subgenome evolution 37 in polyploid ferns. 38